2012
DOI: 10.3354/meps09551
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a future warmer ocean on the coexisting copepods Calanus finmarchicus and C. glacialis in Disko Bay, western Greenland

Abstract: The effects of temperature and food was examined for Calanus finmarchicus and C. glacialis during 3 phases of the phytoplankton spring bloom in Disko Bay, western Greenland. The 2 species were collected during pre-bloom, bloom, and post-bloom and exposed to temperatures from 0 to 10°C, combined with deficient or excess food. Fecal pellet and egg production were measured as indices for grazing and secondary production, respectively. Furthermore, changes in body carbon, nitrogen, and lipid content were measured.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
55
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(67 citation statements)
references
References 59 publications
8
55
3
Order By: Relevance
“…Owing to difficulties of species identification between live C. finmarchicus and C. glacialis, females were selected for experiments and sorted according to the red pigmentation of the antenna and somites . To overcome stress associated with collection, copepods were incubated in 600 ml bottles with an in situ water temperature of 0ºC for 48 h. During the acclimation and experimental periods, copepods were fed the diatom Thalassiosira weissflogii in accordance with Kjellerup et al (2012), the density of copepods was 5 individuals per bottle, and the bottles were capped and rotated once a day. The selected copepod density was slightly lower than in previous experiments (e.g.…”
Section: Sampling and Experimental Set-upmentioning
confidence: 99%
See 1 more Smart Citation
“…Owing to difficulties of species identification between live C. finmarchicus and C. glacialis, females were selected for experiments and sorted according to the red pigmentation of the antenna and somites . To overcome stress associated with collection, copepods were incubated in 600 ml bottles with an in situ water temperature of 0ºC for 48 h. During the acclimation and experimental periods, copepods were fed the diatom Thalassiosira weissflogii in accordance with Kjellerup et al (2012), the density of copepods was 5 individuals per bottle, and the bottles were capped and rotated once a day. The selected copepod density was slightly lower than in previous experiments (e.g.…”
Section: Sampling and Experimental Set-upmentioning
confidence: 99%
“…With ongoing climate change, the northward shift of C. finmarchicus is predicted to continue into Arctic waters currently dominated by C. glacialis and C. hyperboreus (Helaouët et al 2011, Wassmann et al 2011. In addition, warming of the Arctic will likely benefit C. finmarchicus more than C. glacialis (Kjellerup et al 2012), resulting in changes in food-web dynamics and secondary production (Falk-Petersen et al 2007). Despite an extensive knowledge of the ecology and phenology of these 2 species, the molecular basis of physiological responses (particularly changes in gene expression) to increased water temperature remains largely unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…Variance in total zooplankton abundance does not seem to tell the whole story, and some more detailed hypotheses therefore involve the occurrence of qualitative and phenological changes in the food source (Beaugrand et al 2003, Möllmann et al 2003, van der Lingen et al 2006. Climate-induced alterations of the local copepod communities have been reported in both temperate and Arctic regions (Planque & Taylor 1998, Möllmann et al 2003, Beaugrand 2004, Helaouët & Beaugrand 2009, Coyle et al 2011, Kjellerup et al 2012.…”
Section: Introductionmentioning
confidence: 99%
“…The study showed that this population had a strong transcriptomic response to an increase in temperature (from 0°C to 15°C) involving up-regulation of genes related to protein folding, transcription, translation and metabolism, and suggested 5°C as an optimum temperature. Physiological experiments on C. finmarchicus from the same area support this suggestion (Hjorth and Nielsen, 2011;Kjellerup et al, 2012), while studies from warmer areas suggest 10-12°C as an optimal temperature for C. finmarchicus (Harris et al, 2000;Møller et al, 2012). Given these observations and the fact that the distribution of C. finmarchicus is characterised by geographically varying ranges of temperature, salinity and light conditions (Melle et al, 2014), it is likely that response to environmental factors in C. finmarchicus is population-specific.…”
Section: Introductionmentioning
confidence: 93%
“…Experimental manipulation is one way to study a species tolerance to various components of the climate, and to forecast consequences at both the species and ecosystem level. Accordingly, the responses of several Calanus species to various climate stressors such as temperature (Grote et al, 2015;Hildebrandt et al, 2014;Kjellerup et al, 2012;Smolina et al, 2015), ocean acidification (Hildebrandt et al, 2014;Pedersen et al, 2013;Runge et al, 2016;Weydmann et al, 2012), and harmful algal blooms (Lauritano et al, 2012(Lauritano et al, , 2015Roncalli et al, 2016) have already been studied. Within these studies considerable attention has been devoted to temperature, since it affects every aspect of the zooplankton life, from cellular processes to behaviour, development and fitness (Clarke, 2003;Huntley and Lopez, 1992), as well as distributional shifts of Calanus Helaouët et al, 2011;Reygondeau and Beaugrand, 2011a).…”
Section: Introductionmentioning
confidence: 99%